HALAL INDUSTRY FROM THE QUR'AN PERSPECTIVE (ANALYSIS OF Q.S AL-BAQARAH VERSES 168-169 AS A BASIS FOR HALAL PRODUCTS) - Agam, Agam Royana; Al Haddar, Muhsin (UIN Mataram, 2024)
This article wants to respond to halal products based on Q.S al-Baqarah verses 168-169. The author wants to show that society's understanding is directly proportional or not? by using Q.S al-Baqarah verses 168-169 which contains halal and haram foods. In explaining this article the author uses a comparative method, be it interpretation or other research opinions. In his conclusion, the author concludes that people basically do not pay much attention to Q.S al-Baqarah verses 168-169 when consuming a product, it is enough to know that the product is halal and guaranteed by the seller, so people will use it, even products that are not labeled halal are still consumed with local environmental requirements believe the product is halal. Keywords: Product Halal, Exegesis, Q.S al-Baqarah ayat 168-169